2020
DOI: 10.1155/2020/6834591
|View full text |Cite
|
Sign up to set email alerts
|

Visual Binocular Disorders and Their Relationship with Baropodometric Parameters: A Cross-Association Study

Abstract: The aim of this study was to establish a relationship between nonstrabismic binocular dysfunction and baropodometric parameters. A total of 106 participants underwent binocular vision assessment by evaluating horizontal heterophoria, horizontal and vertical fusional vergence ranges, and vergence facility. Posturography was measured using the FreeMED baropodometric platform. Among the variables that the software calculates are foot surface, foot load, and foot pressure. Our results showed that in the participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
5
0
1
Order By: Relevance
“…Additionally, we also observed that most of the foot zones of the legally blind participants had no significant pressure differences compared to controls, except for the higher maximum pressures in the first and second metatarsal heads (M1 and M2 zones) in patients in the closed-eye condition. These differences could be attributed to the contribution of the acquired blind participants’ data [ 15 ]. The small number of significant differences indicates that mild disturbances in the motor control of the balance are present and maybe can be ignored in conventional evaluation of the balance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we also observed that most of the foot zones of the legally blind participants had no significant pressure differences compared to controls, except for the higher maximum pressures in the first and second metatarsal heads (M1 and M2 zones) in patients in the closed-eye condition. These differences could be attributed to the contribution of the acquired blind participants’ data [ 15 ]. The small number of significant differences indicates that mild disturbances in the motor control of the balance are present and maybe can be ignored in conventional evaluation of the balance.…”
Section: Discussionmentioning
confidence: 99%
“…Some research finds that people with visual deficits have impaired balance control [ 16 , 17 ], while other research finds minor or no differences in static and dynamic postural control between sighted and visually impaired subjects [ 13 , 18 , 19 , 27 ]. Subjects with altered binocular vision have been found to have significantly altered measures of foot plantar pressures, and blind subjects can have prolonged foot-to-ground contact during gait [ 15 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Из трех основных компонентов сенсорного обеспечения устойчивости вертикальной позы систематическое изучение роли зрения началось раньше всего [23]. Отмечена корреляция между нарушениями равновесия и некоторыми глазодвигательными нарушениями, а также остротой зрения и расстоянием между глазами и наблюдаемым объектом [24][25][26]. В норме при закрывании глаз (например, во второй фазе пробы Ромберга) существенных позных колебаний не возникает, что говорит о достаточных сочетанных компенсаторных возможностях проприоцепторов и вестибуляров [27,28].…”
Section: зрение и тест ромбергаunclassified
“…The authors (19) report significant changes in plantar pressure in adults with hip osteoarthritis (OA / hip osteoarthritis) in the sense that they show a lower load on heels / rearfoot than healthy ones during static examination (standing still / standing). The use of baropodometry allows the identification of the connections between the dysfunctions of the musculoskeletal system and the visual problems, in those with unstable binocular vision being signaled significant differences between the total areas of the left leg vs. right leg, forefoot area, forefoot load and rearfoot load, according to (20). The postural stability is low when the examination of subjects is done with maximum mouth opening, when there is a lower load of the left calcaneus and a higher load on the left 5 metatarsal head, and the highest values are obtained for the testing situation at the time of swallowing (maximum intercuspation), according to (21).…”
mentioning
confidence: 99%